Ethical Problems with the Preimplantation Genetic Diagnosis of Human Embryos - Alvarado Marambio, José Tomás; Santos Alcántara, Manuel J. (Acta Bioethica, 2018)
The purpose of preimplantation genetic diagnosis by embryonary biopsy is to identify genetic alterations prior to the implantation of embryos produced by in vitro fertilization. The most important aim is the selection of genetically healthy embryos due to their genetic indemnity, but it can also be used to select the sex or, eventually, other detectable traits accrding to the wishes of the parents. This procedure has been the subject of scientific debates, in relation to the harm that it can cause to healthy embryos that are going to be implanted, and in relation to the interpretation of the genetic tests made. Ethical debates have also focused on the production of and respect for the life and the integrity of developing human beings. In this work, it is argued that most of the uses of PGD are morally reprehensible, because they are done with disregard to the dignity that should be granted to embryos as human persons.